THE VALUES OF ISLAMIC RELIGIOUS EDUCATION IN THE NOVEL ''JANJI'' BY TERELIYE AND ITS RELEVANCE TO EDUCATION - Mubarak, A. Faizul; Arizani Humairo (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study is to find and understand the values of Islamic religious education found in “Janji” by Tere Liye, as well as how these values can be internalized by readers as moral messages. By understanding these values, readers are expected to build a character that is not only academically intelligent, but also moral and caring towards society. The novel “Janji” shows that literature has the ability to deliver interesting and inspiring moral messages, especially regarding the character crisis plaguing the younger generation. This research focuses on the importance of overcoming the character education crisis by transforming religious values to strengthen students' morals and ethics. In this context, novels as an educational medium can serve as a tool to instill positive attitudes and values necessary for students' character growth. This study finds and analyzes the elements of Islamic religious education values in the novel by using qualitative methodology and text analysis techniques. The results show that character education values are incorporated into the curriculum, the role of teachers, character development programs, and social activities and community support. This writing is expected to provide useful recommendations for educators and educational practitioners on how to incorporate religious values into the learning process. This will result in a more thorough education program with a focus on moral and cognitive aspects.